Efficacy of a self‐help parenting intervention for parents of children with attention deficit hyperactivity disorder in adjunct to usual treatment—Small‐scale randomized controlled trial. (2nd December 2020) - Daley, David; Tarver, Joanne; Sayal, Kapil
Abstract: Background: Multimodal intervention incorporating psychosocial intervention and medication is recommended for school‐aged children with attention deficit hyperactivity disorder (ADHD). This randomized controlled trial (RCT) investigates the adjunctive benefit of the self‐help version of the New Forest Parenting Programme (NFPP‐SH) when offered in addition to treatment as usual (TAU) compared with TAU alone. Method: Fifty‐two children, receiving medication for ADHD as part of their usual care, were randomized to receive NFPP‐SH + TAU or TAU alone. Results: When used in adjunct to TAU, NFPP‐SH may have beneficial effects for parenting efficacy ( F = 6.28, p = 0.02), child social performance in school and negative comments made by parents during a recorded speech sample. However, the self‐help intervention did not have any additional effect on child behaviour. Conclusions: This study provides further support for self‐help interventions as potentially low‐intensity and cost‐effective alternatives to therapist‐led parenting interventions. The findings require replication in larger samples before any firm conclusions about adjunctive efficacy of NFPP‐SH can be drawn but underline the potential for self‐help within routine treatment (ClinicalTrials.gov Identifier: NCT02174952).